2003
DOI: 10.1080/00365510310003265
|View full text |Cite
|
Sign up to set email alerts
|

Serum lysophosphatidic acid concentrations measured by dot immunogold filtration assay in patients with acute myocardial infarction

Abstract: In this study the relation between lysophosphatidic acid (LPA) and myocardial infarction was investigated, the typical and simplified methods for measuring serum LPA concentration by dot immunogold filtration assay (DIFA) based on a polyclonal antibody to LPA were developed, and serum LPA concentrations were measured in 31 patients with acute myocardial infarction (AMI) and 12 controls (blood donors) by DIFA. Serum LPA levels were raised more than twofold 8 h after the onset of AMI. Maximal elevation (10.43 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 11 publications
3
43
0
1
Order By: Relevance
“…24 Additionally, LPA also plays an important role in the occurrence and development of heart and cerebrovascular disease and kidney disease. 25,26 Our study found that the levels of MCP-1, Cr, and BUN and Paller's score were much lower in LPA treatment group than in 4 h I/R group (p < 0.01), indicating that LPA can reduce renal damage and protect renal function. The likely mechanism is that during renal I/R injury, LPA can inhibit the body to produce a variety of chemotactic factors, which prevent mononuclear macrophage infiltration into renal tissue, and meanwhile LPA also plays a role in antiapoptosis.…”
Section: Discussionmentioning
confidence: 61%
“…24 Additionally, LPA also plays an important role in the occurrence and development of heart and cerebrovascular disease and kidney disease. 25,26 Our study found that the levels of MCP-1, Cr, and BUN and Paller's score were much lower in LPA treatment group than in 4 h I/R group (p < 0.01), indicating that LPA can reduce renal damage and protect renal function. The likely mechanism is that during renal I/R injury, LPA can inhibit the body to produce a variety of chemotactic factors, which prevent mononuclear macrophage infiltration into renal tissue, and meanwhile LPA also plays a role in antiapoptosis.…”
Section: Discussionmentioning
confidence: 61%
“…Immunogold has been applied for immunological detection for a long time, and its advantages include short detection time, low cost, and no requirement for special instruments [13][14][15][16][17] . We have compared our microarray with ELISA according to these aspects: (1) detection with microarray for 96 samples only takes 100 min, whereas the ELISA method takes 2.5-3.5 h; (2) preparing a microarray only needs 10-20 ng of antigen, whereas ELISA needs 100-200 ng, and (3) identification of microarray results does not need any special instruments, whereas the ELI-SA method needs an enzyme immune analyzer.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the serum LPA level in multiple myeloma patients was significantly higher than in normal controls (22), while it is increased in patients with acute myocardial infarction (23). The usage of serum samples, however, may not be suitable; the reported LPA values must have included LPA produced in vitro during sample preparation.…”
mentioning
confidence: 99%